Método para determinação da capacidade e de medidas de desempenho em segmentos de rodovias de pista simples com obras - Rafael Quintão de Andrade (2021)
Work execution on two-lane highway segments requires the closure of the lane in one direction, while the remaining lane operates alternately for both traffic directions. Among the main effects of this operation, called Stop and Go, the increase in travel times for users and the formation of vehicle platoons stand out. Although these interventions are quite frequent on two-lane highways, research on this subject is still incipient. Thus, the present study proposes a method for determining capacity and measures of effectiveness on two-lane highways in work zones. Therefore, a deterministic mathematical formulation was developed, based on Queue Theory and on the similarities with the queue discharge flow that occur at traffic lights, which allows for the estimation of measures of effectiveness such as delay and platoon size. Equations were also developed to determine the capacity and the maximum length of the work zones, based on acceptable values of measures of effectiveness. In the data collection step, control points of interventions were recorded, in which it was possible to obtain traffic data, such as flow, headway, average speed and lost time to start-up. In addition, the vehicle records of a loop inductive were analyzed during the execution of works to establish the desired speeds according to the class of vehicles. This dataset was used to calibrate and validate the traffic simulator Aimsun Next. With the simulator calibrated, a set of synthetic data was generated, based on the simulation of different demand scenarios, percentage of heavy vehicles and lengths of the work zones. These data served both to obtain variables of the problem (such as saturation flow, average speed and passenger car equivalents for trucks) and to validate the proposed method. Measures of effectiveness such as cycle, platoon size and delay were compared, which showed satisfactory results in the validation step. The method developed, therefore, can be applied to predict the average delays of users and the average sizes of platoons formed by cycles of “STOP” and “GO”, depending on the characteristics of the segment in workzone and the estimated vehicle flows.